Perforated flaps of different tissue composition in open shin injury surgery - F. V. Svetlov; A. M. Fayn; D. A. Kisel'; R. N. Akimov; K. I. Skuratovskaya; N. V. Yarygin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Despite the successes and achievements of modern traumatology, the  method  of  microsurgical autotransplantation of tissue complexes remains an urgent topic today. Unfortunately, in various situations, for various reasons, it is not possible to perform microsurgical surgery. The best results of the implantation of free autografts are achieved provided that the defect plastic is performed early, in the acute phase of the wound process, when the wound is contaminated but not yet microbially colonized. Often, the general condition of the victim does not allow for autotransplantation, since an open injury to the lower leg may be part of a multiple or combined injury. There is a contradiction between the need to close a soft tissue defect and the very possibility of performing a large reconstructive operation. The aim is to study and analyze currently existing studies on the use of reconstructive plastic surgery using perforant flaps in patients with a traumatological profile. Highlighting the main directions that can be applied in clinical practice, reviewing and delving into the technical aspects of this method of surgical treatment.Materials and methods. The search for literary sources was carried out using the bibliographic databases of eLibrary.RU, PubMed, Google Scholar and Scopus.Conclusion. Thanks to the review, the main directions of soft limb transplantation were identified. The search for solutions to the problem of treating soft tissue defects in the lower third of the lower leg is far from complete. An in-depth study of the possibilities of perforant skin fascial flaps will allow us to obtain a tool with which it will be possible to improve the results of surgical treatment of this group of patients.